Macro-engineering : MIT Brunel lectures on global infrastructure - Davidson, Frank Paul, 1918-; Grankel, Ernst G.; Meador, C. Lawrence (Horwood engineering science series., 2011)
This volume makes available a reflection on large-scale engineering for building a better world. International authorities from engineering, oceanography, academia, public service, and law describe how great and imaginative concepts may be refined, tested, adapted, financed, implemented and put to use. Here are records and commentaries about some of the world's significant engineering achievements, including the planning and design of Nigeria's new capital city, and the use of software by the US military to clean up the Exxon-Valdez oil spill pollution in Alaska. Describes a method of large-scale engineering for building a better worldProvides records and commentaries about significant engineering achievementsInternational authorities from engineering, oceanography, academia, public service and law describe how great and imaginative concepts may be refined, tested, adapted, financed and implemented.